Response of degraded vegetation to introduction of prescribed burning or mowing management in a Mongolian steppe. (3rd December 2015) - Koyama, Asuka; Kubo, Daisuke; Yoshihara, Yu; Jamsran, Undarmaa; Okuro, Toshiya
Abstract: The understanding of the effectiveness of prescribed burning and mowing as restoration tools of degraded grasslands is important for dryland rangeland management. We examined the effects of spring prescribed burning or seasonal mowing treatments on the degraded vegetation dominated by an unpalatable subshrub, Artemisia adamsii, in grazed Mongolian steppe. Spring burning was conducted in 2013, and three types of mowing treatments (spring, previous summer, and previous summer and autumn) were conducted with varying seasons and frequency, respectively. Soil samples were collected immediately after the spring treatments. Four months after the spring treatments, total plant biomass, the numbers of flowering shoots and florets per shoot of A. adamsii were compared among the treatments. Plant biomass was divided into A. adamsii and herbaceous plants (forbs and graminoids) with different Raunkiaer life forms (chamaephytes, hemicryptophytes and geophytes). Soil properties and total plant biomass were not different among the treatments. For A. adamsii, the biomass and number of flowering shoots were decreased by spring burning and growing‐season mowing, owing to the disappearance of woody‐shoots of A. adamsii . On the other hand, spring mowing had less negative impact on the biomass of A. adamsii due to an increase of the newly‐formed shoots. The biomass of perennial herbaceous‐plants was not affected by spring burning, regardless of the life form, whereas that of the geophytic sedge Carex duriuscula increased in the summer‐and‐autumn mowing. Thus, spring burning and growing‐season mowing have the potential to control undesirable subshrubs due to loss of the woody shoots, while spring mowing may not be recommended as a useful management tool in the Mongolian steppe. Our results emphasize that the introduction of these management tools for degraded‐grassland restoration in dryland rangelands needs more long‐term evaluation considering the relation with external factors such as climate variation and grazing impact.